Копірайтинг та візуалізація в соціальному маркетингу на прикладі української реклами про захист тварин - Ткачук (Стахурська), Світлана Валеріївна (My University, 2024)
У статті досліджується специфіка копірайтингу та візуального ряду у соціальному маркетингу на прикладі української соціальної реклами про захист тварин. Соціальна реклама такого типу розглядається як важливе суспільне явище, а проблема, яку вона висвітлює, потребує популяризації та пошуку шляхів вирішення. Окрема увага приділена складовим впливу на свідомість читача у рекламних повідомленнях про захист тварин. Виявлено, що така соціальна реклама в Україні має місце і розвивається. У рекламних зверненнях присутні необхідні чинники впливу успішної соціальної реклами. Розглянуті окремі рекламні кампанії, зокрема й після початку повномасштабних бойових дій, коли небезпека для людей і тварин явно збільшилась. Також виявлені резерви удосконалення соціальної реклами про захист тварин, зокрема посилення інформаційної компоненти щодо реальних шляхів допомоги тваринам, посилення когнітивної складової й емоційного зв’язку між благом тварин і благом людей, розрив і знищення стереотипів протиставлення цих двох благ. Також серед резервів актуалізації й вирішення проблеми негуманного ставлення до тварин пропонується нативна популяризація гуманного ставлення, висвітлення у рекламних комунікаціях реальних шляхів допомоги тваринам, посилення акценту на взаємозв’язку блага тварини і блага людини, поєднання допомоги тваринам із дозвіллям тощо.

The article examines the specifics of copywriting and visualization in social marketing using the example of Ukrainian social advertising about animal protection. Social advertising of this type is considered as an important social phenomenon, and the problem it highlights needs to be popularized and find solutions. Particular attention is paid to the components of influence on the reader's consciousness in advertising messages about animal protection, in particular emotional, communicative, cognitive, motivational and other types of influence. It has been established that such social advertising takes place and is developing in Ukraine. Advertising appeals have the necessary influencing factors for successful social advertising. Individual advertising campaigns were studied, particularly after the start of full-scale hostilities, when the danger to people and animals clearly increased. Reserves for improving social advertising about animal protection have also been determined, in particular, strengthening the informational component about real ways to help animals, strengthening the cognitive component and the emotional connection between the welfare of animals and the welfare of people, breaking and destroying stereotypes about the opposition of these two benefits. Also, among the reserves of updating and solving the problem of inhumane treatment of animals, one can name the popularization of humane treatment, highlighting in advertising communications real ways of helping animals, increasing emphasis on the relationship between animal welfare and human welfare, combining animal welfare with leisure, etc. It is proposed to continue and expand the experience of creating communities in social networks and messengers, which in a native form popularize the rules of pet care, and also provide real contacts to whom you can turn for help. In addition, it is important to expand the circle of animals for which the issue of proper maintenance and care needs to be raised, in particular through social advertising tools. We are talking about rodents, rabbits, birds and other domestic animals, questions about the proper maintenance of which are almost never raised.
Keywords: копірайтинг соціальної реклами; копірайтинг; маркетинг; соціальний маркетинг; захист тварин; реклама про захист тварин; візуалізація в рекламі; копірайтинг в рекламі; copywriting; social advertising copywriting; marketing; social marketing; animal protection; advertising about animal protection; visualization in advertising; copywriting in advertising; кафедра маркетингу